Energy Resource Management Model in a Hotel Building Using a Web Platform - Sousa, Tiago (2021)
Distributed generation and demand response have been fostered in the last years, sometimes less than desired. In fact, these energy resources, which have a distributed nature have been mostly applied and discussed in the wide view of the operation and planning of the distribution system. However, a great potential is now being explored in the scope of buildings energy management. In the present paper, an energy resource management model has been implemented in order to be integrated with a web platform that supports the customer information concerning energy usage. The model can be used for several kinds of buildings. A hotel building is focused in this paper, namely in the case study that discusses the use of each resource, including photovoltaic generation and demand response.